The value of ultrasound combined with CT in identifying early low-grade appendiceal mucinous neoplasm and appendicitis - Bai, Dong; Zhou, Nan; Dou, Ruixue; Wang, Jiajun; Zhang, Pu; Wang, Haoyu; Wang, Zhiqun; Liang, Lei (Frontiers in Oncology, 2023)
Author contribution statement Lei Liang and Zhiqun Wang conceived and designed the experiments; Dong Bai # and Nan Zhou # equally contributed to this work, and they jointly completed the study design, data collection, statistical analysis, and article writing; Ruixue Dou, Pu Zhang, and Haoyu Wang mainly completed the data collection work; Jiajun Wang completed the data analysis and chart production. All authors contributed to the article and approved the submitted version.Objective: To investigate the value of ultrasound combined with CT in identifying early low-grade appendiceal mucinous neoplasm and appendicitis. Methods: Patients with early low-grade appendiceal mucinous neoplasm and appendicitis from September 2017 to September 2021, including 40 with low-grade appendiceal mucinous neoplasm and 40 with appendicitis, were collected in this study. Clinical data, ultrasound and CT findings of all patients were retrospectively analyzed. Univariate and multivariate logistic regression analyses were applied to establish the ultrasound model, CT model and combined model. Results: The nomogram showed specific characteristics of CT were dilated appendiceal diameter and clear surrounding fat space in the low-grade appendiceal mucinous neoplasm, as well specific characteristics of ultrasound were thin or clear layer appendix wall, and flocculent echo in the appendix cavity. These four features were used to construct a nomogram for predicting early low-grade appendiceal mucinous neoplasm, and the AUC value was 0.839. Conclusion: Ultrasound combined CT for diagnosis of early low-grade appendiceal mucinous neoplasm has significant value, when found significantly dilated appendix in right lower abdominal, with thin wall, wall calcification, clear surrounding fat space, progressive enhancement, especially non-specific symptoms similar to appendicitis, the physician should timely consider the possibility of low-grade appendiceal mucinous neoplasm.